p, T, E-diagram of Sn₂P₂S₆ ferroelectric with high-pressure incommensurate phase - Kedyulich, V.M.; Slivka, A.G.; Gerzanich, E.I.; Shusta, V.S. (Condensed Matter Physics, 2000)
The investigations on the temperature change in dielectric permeability of Sn₂P₂S₆ crystal at different misaligning electric ﬁelds and hydrostatic pressures have been carried out to establish the form of p, T, E-diagram for this crystal. Based on the investigations on dielectric permeability anomalies, the E, T -diagrams at different magnitudes of hydrostatic pressure and p, T, E-diagram of Sn₂P₂S₆ crystal have been constructed. The magnitudes of coefﬁcients in the thermodynamic potential expansion have been estimated and coordinates of critical points in E, T -diagrams have been deﬁned.